Extracellular Matrix Remodeling During Palate Development. (2nd April 2020) - Wang, Xia; Li, Chunman; Zhu, Zeyao; Yuan, Li; Chan, Wood Yee; Sha, Ou
ABSTRACT: The morphogenesis of the mammalian secondary plate is a series of highly dynamic developmental process, including the palate shelves vertical outgrowth, elevation to the horizontal plane and complete fusion in the midline. Extracellular matrix (ECM) proteins not only form the basic infrastructure for palatal mesenchymal cells to adhere via integrins but also interact with cells to regulate their functions such as proliferation and differentiation. ECM remodeling is essential for palatal outgrowth, expansion, elevation, and fusion. Multiple signaling pathways important for palatogenesis such as FGF, TGF β, BMP, and SHH remodels ECM dynamics. Dysregulation of ECM such as HA synthesis or ECM breakdown enzymes MMPs or ADAMTS causes cleft palate in mouse models. A better understanding of ECM remodeling will contribute to revealing the pathogenesis of cleft palate.